Exosomal PVRL4 Promotes Lung Adenocarcinoma Progression by Enhancing the Generation of Myeloid‐Derived Suppressor Cell‐Secreted TGF‐β1 - Yahai Liang; Jinmei Li; Lihua Zhang; Jinling Zhou; Meilian Liu; Xiaoxia Peng; Weizhen Zheng; Zhennan Lai (Thoracic Cancer)
ABSTRACT Background The cancer cell marker poliovirus receptor‐like protein 4 (PVRL4) has been shown to be highly expressed in many cancers, including lung cancer. Myeloid‐derived suppressor cells (MDSCs) are a population of immature myeloid cells with immunosuppressive roles that can attenuate the anticancer response. Here, the precise functions and the relationship between PVRL4 and MDSCs in lung adenocarcinoma (LUAD) progression were investigated. Methods Detection of levels of mRNAs and proteins was conducted using qRT‐PCR and western blotting. The CCK‐8, colony formation, transwell, wound healing assays, and flow cytometry were used to explore cell growth, invasion, migration, and apoptosis, respectively. ELISA analysis detected TGF‐β1 contents. LUAD mouse models were established for in vivo assay. Exosomes were isolated by ultracentrifugation. MDSCs were induced from peripheral blood mononuclear cells (PBMCs) by cytokine or co‐culture with cancer cells. Results LUAD tissues and cells showed high PVRL4 expression, and PVRL4 deficiency suppressed LUAD cell proliferation, invasion, migration, and induced cell apoptosis in vitro, and impeded LUAD growth in vivo. Thereafter, we found that PVRL4 was packaged into exosomes in LUAD cells, and could be transferred into PBMCs to promote MDSC induction and the expression of MDSC‐secreted TGF‐β1. Functionally, the silencing of exosomal PVRL4 impaired LUAD cell proliferation, invasion, migration, and evoked cell apoptosis, which could be reversed by the incubation of TGF‐β1‐overexpressed MDSCs. Conclusion Exosomal PVRL4 promoted LUAD progression by inducing the secretion of TGF‐β1 in MDSCs, indicating a novel direction for LUAD immunotherapy.